Effects of elevated atmospheric CO2 concentration on growth and photosynthesis in eddo at two different air temperatures - Md Akik Bin Zaher; Etsushi Kumagai; Takayuki Yabiku; Miyuki Nakajima; Toshinori Matsunami; Nobuhiko Matsuyama; Nguyen Cong Thinh; Toshihiro Hasegawa; Michio Kawasaki (Plant Production Science, 2021)
Future agricultural management programs should consider the responsiveness of crops to increasing atmospheric CO2 concentrations ([CO2]) and temperatures. Eddo is an important tuber crop widely grown in Asia, but its response to [CO2] and temperatures remains largely unknown. We investigated the responses of eddo and rice plants to elevated [CO2] (ambient [CO2] + 200 µmol mol−1) at low and high temperatures during the early-to-intermediate growth stage in temperature gradient chambers in 2018 and 2019. The dry weights (DWs) of the eddo leaf blades, petioles, roots, and above-ground parts as well as the DWs of the rice leaf blades, leaf sheaths and stems, above-ground parts, and whole plants significantly increased under elevated [CO2]. The number of leaves, leaf area, and SPAD value of eddo significantly increased under elevated [CO2], whereas the leaf area and SPAD value of rice did not. The net photosynthetic rate of eddo and rice tended to increase under elevated [CO2]. The increasing ratio of the total DW in elevated vs ambient [CO2] was significantly higher for eddo than for rice. The result indicates that elevated [CO2] increases the eddo biomass more than the rice biomass, possibly because of the increasing eddo leaf area and SPAD value induced by elevated [CO2]. The total DW of rice increased significantly in response to the high air temperature under elevated [CO2] conditions. However, the effect of [CO2] on the total DW of eddo was similar at both temperatures, reflecting the non-significant interaction between [CO2] and temperature. Abbreviations: [CO2]: atmospheric carbon dioxide concentration, DW: dry weight, FACE: free-air CO2 enrichment, gs: stomatal conductance, PN: net photosynthetic rate, TGC: temperature gradient chamber